1979
DOI: 10.1136/gut.20.5.394
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous prostaglandins in peptic ulcer disease.

Abstract: SUMMARY Plasma concentrations of prostaglandins E and F have been measured by radioimmunoassay in patients undergoing diagnostic upper intestinal endoscopy. The results fail to support a previously reported deficiency of plasma PGE in duodenal ulcer patients. Plasma prostaglandin concentrations failed to correlate with the parameters of gastric secretion studied; and were unaffected by histamine H2-receptor blockade or the activity of duodenal ulceration. During combined pentagastrin and insulin secretory stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The levels of plasma prostaglandins found in our control patients are higher than those found in healthy adults (12,13), although they were similar to those described by Yamashiro et al in a recent pediatric study (14). We did not find any difference in plasma prost aglandin between children of different age in our study.…”
Section: Gastric Juice Prostaglandinssupporting
confidence: 87%
“…The levels of plasma prostaglandins found in our control patients are higher than those found in healthy adults (12,13), although they were similar to those described by Yamashiro et al in a recent pediatric study (14). We did not find any difference in plasma prost aglandin between children of different age in our study.…”
Section: Gastric Juice Prostaglandinssupporting
confidence: 87%
“…The gastric mucosal PG level in patients with gastric ulcer was lower than the normal volunteers (15,16). There was no difference between the levels found in the patients with duodenal ulcer and those of the normal volunteers (16)(17)(18). These findings raise the possibility that OPC-12759, in causing an increment in gastric mucosal PG content, may prove to be a useful anti gastric ulcer agent.…”
Section: Discussionmentioning
confidence: 44%
“…Rachmilewitz et al 27 ) and Sharon P et al 28 ) found that cultured gastric and duodenal mucosa synthesized significantly less prostanoids in duodenal ulcer patients and they concluded that a decrease in endogenous prostanoid synthesis might have an important pathogenic role in peptic ulcer diseases. In contrast to these observations, Schlegel et al 19 ) reported higher levels of the mucosal prostaglandin in gastric ulcer patients than normals and Tonnesen et al 29 ) , Cheung et al 2 ) , Ligumsky et al 21 ) , and Baker et al 30 ) had failed to confirm this PGE deficiency in patients with duodenal ulcer.…”
Section: Discussionmentioning
confidence: 94%